The Role of Human Immunodeficiency Virus in Influenza- and Respiratory Syncytial Virus–associated Hospitalizations in South African Children, 2011–2016. (29th June 2018) - McMorrow, Meredith L; Tempia, Stefano; Walaza, Sibongile; Treurnicht, Florette K; Moyes, Jocelyn; Cohen, Adam L; Pretorius, Marthi; Hellferscee, Orienka; Wolter, Nicole; von Gottberg, Anne; Nguweneza, Arthemon; McAnerney, Johanna M; et al.
Abstract: Background: Data describing influenza– or respiratory syncytial virus (RSV)–associated hospitalized illness in children aged <5 years in Africa are limited. Methods: During 2011–2016, we conducted surveillance for severe respiratory illness (SRI) in children aged <5 years in 3 South African hospitals. Nasopharyngeal aspirates were tested for influenza and RSV using real-time reverse transcription polymerase chain reaction. We estimated rates of influenza- and RSV-associated hospitalized SRI by human immunodeficiency virus (HIV) status and compared children who tested positive for influenza vs RSV using multivariable penalized logistic regression. Results: Among 3650 hospitalized children, 203 (5.6%) tested positive for influenza viruses, 874 (23.9%) for RSV, and 19 (0.5%) for both. The median age of children hospitalized with influenza was 13.9 months vs 4.4 months for RSV ( P < .01). Annual influenza-associated hospitalization rates per 100000 were highest among infants aged 6–11 months (545; 95% confidence interval [CI], 409–703), while RSV-associated hospitalization rates were highest in infants aged 0–2 months (6593; 95% CI, 5947–7217). HIV exposure was associated with increased incidence of influenza- and RSV-associated hospitalization in infants aged 0–5 months, with relative risk (RR) 2.2 (95% CI, 1.4–3.4) and 1.4 (95% CI, 1.3–1.6), respectively. HIV infection was associated with increased incidence of influenza- and RSV-associated hospitalization in all age groups; RR 2.7 (95% CI, 2.0–3.5) and 3.8 (95% CI, 3.1–4.8), respectively. Conclusions: Influenza- and RSV-associated hospitalizations are common among South African infants. HIV infection and HIV exposure in infants increase risk of influenza- and RSV-associated hospitalization. Abstract : While human immunodeficiency virus (HIV) infection is a known risk factor, this is the first study to demonstrate that HIV exposure is also a risk factor for influenza- and Respiratory Syncytial Virus-associated hospitalization in infants aged 0–5 months.